1973
DOI: 10.1037/h0035365
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and ethical problems of evaluating the influence of hypnosis in antisocial conduct.

Abstract: The study attempted to improve upon the procedures of an earlier experiment in isolating the effects of hypnosis, a personal relationship, and the knowledge of an experiment on influencing antisocial conduct. A measure of a subject's moral stance toward the specific antisocial act (selling heroin) was also obtained. The results suggest that the experimental manipulations were general!}' successful in deceiving subjects into believing that the antisocial request was separate from an experiment, and that a subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…California State University suggests that Orne's contentions may not be entirely accurate. In a recently reported experiment (Coe, et al ., 1973) these researchers appear to have convinced a majority of their Ss that the requested antisocial act would be performed in a natural, and hence threatening context. However, as the Es point out, "there is no way to conduct research of this kind without risk .…”
Section: Please Scroll Down For Articlementioning
confidence: 91%
“…California State University suggests that Orne's contentions may not be entirely accurate. In a recently reported experiment (Coe, et al ., 1973) these researchers appear to have convinced a majority of their Ss that the requested antisocial act would be performed in a natural, and hence threatening context. However, as the Es point out, "there is no way to conduct research of this kind without risk .…”
Section: Please Scroll Down For Articlementioning
confidence: 91%
“…Significantly, whereas five of six participants carried out the acts when hypnotized, only two of the same participants carried out the acts when not hypnotized; however, all six nonhypnotic simulators carried out the tasks. Other studies have shown that nonhypnotic participants are just as likely as (and sometimes slightly more likely than) hypnotic participants to perform a variety of antisocial or repugnant acts including mutilating the bible, cutting up the national flag (Levitt, Aronoff, Morgan, Overley, & Parrish, 1975), signing derogatory-slanderous statements about a superior (Calverley & Barber, 1965, cited in Barber, 1969, and even dealing heroin (Coe et al, 1972(Coe et al, , 1973. These results fit in with a variety of other evidence that indicates that participants, regardless of whether hypnosis is used, are highly motivated to respond to the demands of the particular context (Orne, 1962(Orne, , 1970Wagstaff, 1981) and will readily perform what appear to be dangerous and antisocial acts if required to do so (see, for example, Milgram, 1974;Sheridan & King, 1972).…”
Section: Hypnotic Coercion In the Laboratorymentioning
confidence: 99%
“…However, a number of reviewers of these studies have concluded that the notion of a hypnotic state is not necessary to explain these effects; rather, they occurred because either, contrary to outward appearances, participants perceived the situation to be safe or they considered that someone else would take responsibility for their actions (Barber, 1961(Barber, , 1969Coe, Kobayashi, & Howard, 1972, 1973Orne & Evans, 1965;Udolf, 1983).…”
Section: Hypnotic Coercion In the Laboratorymentioning
confidence: 99%
“…However, these views of the coercive powers of hypnosis seem, on the whole, to contrast with the findings from hypnosis research. For instance, a number of studies have shown that non-hypnotic participants are just as likely as (and sometimes slightly more likely than) hypnotic participants to perform a variety of antisocial or repugnant acts that have included making slanderous statements, plunging their hands into a beaker of acid and throwing the acid at the experimenter, mutilating the bible, cutting up the national flag, making a homosexual approach, and even heroin dealing (Calverley & Barber, 1965; Coe, Kobayashi & Howard, 1972, 1973; Levitt, Aronoff, Morgan, Overley & Parrish, 1975;O'Brien & Rabuck, 1976, Orne & Evans, 1965. O n the basis of such studies many investigators have come to the conclusion that participants do not lose consciousness, control of their behaviour, or their normal moral scruples, and are no more likely to engage in self-repugnant or antisocial activities than equivalently motivated non-hypnotic participants (Barber, 1961(Barber, , 1969Conn, 1972;Gibson, 1991;Hartland, 1974;Kline, 1958;Udolf, 1983;Vingoe, 1992;Wagstaff, 1991u,b, 1993Wolberg, 1972).…”
mentioning
confidence: 99%